2013
DOI: 10.1016/j.msea.2013.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of an austenite NiTi shape memory alloy treated with laser induced shock

Abstract: a b s t r a c tIn this study, microstructure and mechanical properties of an austenite NiTi alloy treated with laser shock peening (LSP) was investigated. It was found that the thickness of shock affected layer is about 250-300 μm. The surface hardness of the specimen is increased by approximately 10% after LSP. Laser induced shock introduces slightly residual compressive stress in the peened specimen. The superleastic stress-strain curves of the fully LSP processed NiTi material show no change in phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Liao et al (2012) obtained the evidence of martensitic transformation during laser shock process using the TEM and XRD characterizations of postmortem specimen. Our previous study showed that there is only amorphization near the laser shock treated surface in an austenite NiTi target and no residual martensite was observed ( Wang et al, 2013 ). In the present study, the microscopic observation of shocked region showed the evidence of residual martensites for laser power density 3.4 GW/cm 2 and 4.4 GW/cm 2 but no any sign of residual martensites for laser power density 2.6 GW/cm 2 (see Fig.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Liao et al (2012) obtained the evidence of martensitic transformation during laser shock process using the TEM and XRD characterizations of postmortem specimen. Our previous study showed that there is only amorphization near the laser shock treated surface in an austenite NiTi target and no residual martensite was observed ( Wang et al, 2013 ). In the present study, the microscopic observation of shocked region showed the evidence of residual martensites for laser power density 3.4 GW/cm 2 and 4.4 GW/cm 2 but no any sign of residual martensites for laser power density 2.6 GW/cm 2 (see Fig.…”
Section: Discussionsupporting
confidence: 56%
“…The constitutive model of NiTi SMAs is shown in Fig. 7 ( Otsuka and Ren, 2005;Otsuka and Wayman, 1999;Wang et al, 2013 ). For an austenite NiTi alloy, phase transformation from austenite to martensite occurs when the applied stress reaches the phase transition stress ( σ AM s ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth of GHL can be obtained through the microhardness distribution along the cross-section of laser peened sample [10][11][12]. According to Chen et al [21] and Carlsson and Larsson [22], the induced residual compressive stress can enhance the hardness of material.…”
Section: Depth Of the Ghlmentioning
confidence: 99%
“…It was reported by Mats et al [9] that the increase of the impact toughness for the steel 15Kh2NMFA upon high-temperature ultrasonic treatment of various durations is due to the formation of a uniform defect structure. For the LSP processing technology, the mechanical properties of the hardened layer are not uniform [1,2,[10][11][12]. By the micro-hardness tests across the LSP peened layer, Peyre et al [10] reported that the hardness decreases gradually from surface to the base material.…”
Section: Introductionmentioning
confidence: 99%